The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7554/elife.39777
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of hippocampal calcium activity across the sleep-wake cycle

Abstract: Calcium is a critical second messenger in neurons that contributes to learning and memory, but how the coordination of action potentials of neuronal ensembles with the hippocampal local field potential (LFP) is reflected in dynamic calcium activity remains unclear. Here, we recorded hippocampal calcium activity with endoscopic imaging of the genetically encoded fluorophore GCaMP6 with concomitant LFP in freely behaving mice. Dynamic calcium activity was greater in exploratory behavior and REM sleep than in qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 71 publications
11
32
2
Order By: Relevance
“…Signal decomposition into aperiodic and periodic components (Donoghue et al, 2020) showed that the optogenetic stimulation enhanced the periodic components with peaks in the theta and slow gamma bands and decreased the aperiodic component of the signal (1/f background). Our observation of the enhanced thetagamma activity might appear at odds with previous reports that such manipulation does not change theta-gamma power during sleep (Ma et al, 2020) and quiet wakefulness (Zhou et al, 2019). The combined effect of the cholinergic stimulation on the periodic and aperiodic signal sums to near-zero values, which could explain the different conclusions, showing the advantage of PSD decomposition (Donoghue et al, 2020) when assessing the power of periodic signals.…”
Section: Cholinergic Influence On Hippocampal Network Activitycontrasting
confidence: 95%
See 4 more Smart Citations
“…Signal decomposition into aperiodic and periodic components (Donoghue et al, 2020) showed that the optogenetic stimulation enhanced the periodic components with peaks in the theta and slow gamma bands and decreased the aperiodic component of the signal (1/f background). Our observation of the enhanced thetagamma activity might appear at odds with previous reports that such manipulation does not change theta-gamma power during sleep (Ma et al, 2020) and quiet wakefulness (Zhou et al, 2019). The combined effect of the cholinergic stimulation on the periodic and aperiodic signal sums to near-zero values, which could explain the different conclusions, showing the advantage of PSD decomposition (Donoghue et al, 2020) when assessing the power of periodic signals.…”
Section: Cholinergic Influence On Hippocampal Network Activitycontrasting
confidence: 95%
“…Conversely, cholinergic tone and MS cholinergic neuron discharge are at their lowest during slow-wave sleep and wake immobility, which are associated with the highest ripple incidence (Fadda et al, 2000;Ma et al 2020). In accordance with these observations, we found that stimulation of MS cholinergic neurons reduces SWRs both in awake behaving animals and naturally sleeping animals, consistent with previous reports (Figure 4,5;Vandecasteele et al, 2014;Zhou et al, 2019;Ma et al, 2020).…”
Section: Cholinergic Influence On Hippocampal Network Activitysupporting
confidence: 93%
See 3 more Smart Citations